Євгеній Козак (1857-1933): життя та науковий доробок рек-тора Чернівецького університету, професора-славіста, священ-нослужителя (До 150-річчя з дня заснування університету в Чернівцях) - Чучко, Михайло Костянтинович; Грябан, Вікторія Вікторівна; Chuchko, Mykhailo; Hryaban, Viktoriya (Chernivtsi «Druk Art», 2025)
This research represents a comprehensive study of the life and work of the famous Slavic scholar Eugen Kozak (1857–1933). Kozak was rector of Chernivtsi University and a public, political, and religious figure, who had until recently barely attracted any scholarly attention. Kozak’s biography reveals his significance both for the history of Chernivtsi University and for the intellectual and cultural life of Bukovina. At the centre of the latter was located the university and primarily its Slavonic departments, which became a reflection of the significance of Slavic studies both as a scientific discipline and as an instrument of foreign and domestic policy. Based on archival materials, epistolary heritage, published texts, memoirs, and the press, the authors analyse Kozak’s life and scientific achievements in the context of socio-political transformations, which took place in Bukovina in the late nineteenth and early twentieth centuries – during Austrian and Romanian rule. Born into the family of a priest, Kozak chose a spiritual path and received a thorough theological and philological educa-tion. While studying in Vienna, he was a librarian at a Slavic seminar. Under the guidance of Vatroslav Jagic, he expanded the library collection and, together with other colleagues, carried out various research projects on Slavic studies. After becoming a professor at Chernivtsi University, his primary focus became teaching and research. The peak of his academic career was being appointed to the position of vice chancellor of the university. Eugen Kozak was the author of a number of scientific works devoted to the study of ancient Slavic literature and epigraphy of Church-Slavonic monuments preserved in Buko-vina since the Moldavian era. Among them are publications on the apocryphal literature of the Slavs, the antiquities of the monasteries of Sucevita and Putna, and a fundamental monograph on Slavic epigraphy: «Inscriptions from Bukovina». At the same time, E. Kozak was creating and replenishing the funds of the Church Museum of the Metropolis of Buko-vina. In addition to his research and teaching activities, Eugen Kozak was actively involved in public and political work, defending the interests of the Russophile community. In the First World War, E. Kozak and his family were deported to Salzburg because of his political views. After Bukovina became part of Romania, he returned to teaching at the University of Chernivtsi; later, he became a senator in the Romanian parliament. After speaking out against the Romanisation of the Bukovina Metropolis at a church congress, his tenure was revoked. He continued his scientific work until the end of his life, collecting materials for his studies and corresponding with colleagues. The results of the study allow us to better understand Kozak’s role in the development of Ukrainian science and culture as well as the context in which he lived and worked. To a large extent, the study is based on the epistolary heritage of E. Kozak and V. Jagić, which is preserved in the scientific library of the University of Chernivtsi and the collections of the National and University Libraries of Zagreb and which are introduced into scientific circulation by these authors for the first time. Based on this unpublished correspondence, the authors reconstruct the sci-entific discussions, exchange of views, and relationships between the two scholars. These letters are a valuable source for the history of the development of Slavic studies in the late nineteenth and early twentieth centuries in Austria-Hungary and neighboring lands.
Євгеній Козак (1857-1933): життя та науковий доробок рек-тора Чернівецького університету, професора-славіста, священ-нослужителя (До 150-річчя з дня заснування університету в Чернівцях) : монографія. Чернівці : Друк Арт, 2025. 136 с.
Eugen Kozak (1857–1933): life and scientific achievements of the rector of Chernivtsi University, professor of Slavic studies, clergyman To the 150th anniversary of the founding of the university in Chernivtsi. Chernivtsi : Druk Art, 2025. 136 p.
The research was carried out with financial support from the Austrian Science Foundation (FWF) (Grant number I 5309)
Keywords: Eugen Kozak, Bukovina, Chernivtsi University, Slavonic departments, priest, professor rector